Implementasi Fatwa DSN MUI Nomor 31/DSN-MUI/VI/2002 Tentang Pengalihan Utang Di Bank Syariah - Fadillah, Irfan; Widyananto, Arief (LPPM Universitas Islam 45, 2024)
The purpose of this study is to find out whether the application of the debt transfer contract is in accordance with Fatwa DSN MUI and to find out the supporting and obstacles in implementing the debt transfer contract. This type of research is field research using data collection methods in the form of interviews, observations and literature related with the problem under study, both as primary and secondary sources. While the method used is the qualitative description method. The results of this study explain that the application of debt transfer begins with the provision of qardh to customers the buyback process between customers with the bank until the end of the installment installment payment period. While the supporting factors are helping and facilitate customers who want to migrate from conventional banks to Islamic banks. For inhibiting factors is the lack of ability customers in paying installments, the customer's ability to provide the necessary funds related to financing in the debt transfer contract transfer of debt, the house that used as collateral is not feasible based on the appraisal assessment, did not get approval from the bank that will be transferred.